Noninvasive evaluation of HABP1 expression with 99mTc-labeled small-interference RNA in ovarian cancer. (2nd November 2021) - Duan, Chunyu; Gao, Yue; Luan, Sha; Guo, Shibo; Cao, Xueliang; Xu, Peng; Fu, Peng; Zhao, Changjiu
Abstract: Purpose: Ovarian cancer is one of the most common gynecological cancers in women with a low 5-year survival rate. Evaluation of hyaluronic acid-binding protein 1 (HABP1) level can provide important information for the diagnosis and treatment of ovarian cancer. In this study, we designed a novel HABP1 probe based on 99m Tc-radiolabeled small-interference RNA (siRNA) for detecting HABP1 expression noninvasively in vivo, thereby providing a new method for its diagnosis and treatment. Methods: A specific siHABP1 was selected because of its targetability and silencing effect. A negative control siRNA (NCsiRNA) with no homology with the human genome was used. SiHABP1 and NCsiRNA were radiolabeled with 99m Tc using the bifunctional chelating agent hydrazinonicotinamide (HYNIC). The radiochemical purity and in vitro stability of the probe were determined by HPLC. The binding activity was measured by western blotting (WB) and RT-PCR. The HABP1-overexpressing human ovarian cancer cell line HO-8910 was used for cell uptake experiments, which were performed with or without transfection and measured with a gamma counter. HO8910-bearing mice were imaged at 1, 4, and 10 h, and biodistribution analysis was performed at 1, 4, 6, and 10 h after injection of 99m Tc-HYNIC-siRNA. Results: 99m Tc-HYNIC-siHABP1 had high radiochemical purity and good in vitro stability, and showed the same binding capacity and silencing effect as siHABP1. SPECT imaging showed that tumors were clearly visualized at 10 h after injection of 99m Tc-HYNIC-siHABP1 but not after 99m Tc-HYNIC-NCsiRNA, implying specific binding. The biodistribution results were consistent with those of SPECT imaging. Conclusions: We showed that 99m Tc-HYNIC-siHABP1 is a feasible probe for the noninvasive visualization of HABP1 expression in ovarian cancer.